Exploring Tiktok’s Impact on ESP Students’ Speaking Engagement - Erydani, Vinsensia Anisa Citta; Fitriati, Sri Wuli; Widhiyanto, Widhiyanto; Mujiyanto, Januarius; Madjdi, Achmad Hilal (SCAD Independent, 2025)
The growing influence of social media on language acquisition has opened new avenues for enhancing student engagement in foreign language learning. However, its impact on verbal participation remains underexplored. This study investigates the role of TikTok as an instructional tool in English for Specific Purposes (ESP) speaking classes, focusing on its effectiveness in fostering student engagement. Employing a mixed-methods approach, this study integrates quantitative pre-test and post-test assessments to measure engagement levels and qualitative data from semi-structured interviews and focus group discussions to capture students’ perceptions. The findings indicate a significant increase in engagement: statistical analyses reveal notable improvements in students’ participation, while qualitative insights highlight TikTok’s capacity to enhance motivation, peer interaction, and authentic language practice. These results suggest that TikTok is a dynamic platform for improving speaking skills and engagement, offering valuable implications for educators seeking innovative teaching strategies in the digital era.